2023
DOI: 10.1038/s41422-022-00766-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ATAD3A-PINK1-mitophagy axis overcomes chemoimmunotherapy resistance by redirecting PD-L1 to mitochondria

Abstract: Only a small proportion of patients with triple-negative breast cancer benefit from immune checkpoint inhibitor (ICI) targeting PD-1/PD-L1 signaling in combination with chemotherapy. Here, we discovered that therapeutic response to ICI plus paclitaxel was associated with subcellular redistribution of PD-L1. In our immunotherapy cohort of ICI in combination with nab-paclitaxel, tumor samples from responders showed significant distribution of PD-L1 at mitochondria, while non-responders showed increased accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…PD-L1/PD-1 blockade by AMPK activation significantly enhances cancer immunotherapy [ 126 , 127 ]. Pink1 regulates mitochondrial localization of PD-L1 for its degradation via mitophagy [ 128 ].…”
Section: Mitochondria-mediated Various Signaling Pathways and Carcino...mentioning
confidence: 99%
“…PD-L1/PD-1 blockade by AMPK activation significantly enhances cancer immunotherapy [ 126 , 127 ]. Pink1 regulates mitochondrial localization of PD-L1 for its degradation via mitophagy [ 128 ].…”
Section: Mitochondria-mediated Various Signaling Pathways and Carcino...mentioning
confidence: 99%
“…Paclitaxel (PTX) increased ATAD3A expression, which disrupts the stability of PD-L1 by inhibiting PINK1-dependent mitosis. The results of preclinical studies further demonstrated that targeting ATAD3A could reset a favorable anti-tumor immune microenvironment and improve the efficacy of ICI combination therapy, increasing the effectiveness of ICI plus PTX combination therapy [30] .…”
Section: Small Molecules From Natural Productsmentioning
confidence: 99%
“…Furthermore, ATAD3A is also involved in the sensitivity and resistance of tumor drugs. For instance, high levels of ATAD3A expression can reduce the sensitivity of tumor cells to certain chemotherapy drugs, which in turn can impact the effectiveness of tumor treatment 12 . However, the role and regulation mechanisms of ATAD3A in LUAD is still lack of further understanding and research, and its impact on tumor microenvironment is also unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, high levels of ATAD3A expression can reduce the sensitivity of tumor cells to certain chemotherapy drugs, which in turn can impact the effectiveness of tumor treatment. 12 However, the role and regulation mechanisms of ATAD3A in LUAD is still lack of further understanding and research, and its impact on tumor microenvironment is also unknown. Therefore, further studies of ATAD3A and the effect of its specific inhibitors in LUAD will help understand its mechanism and potential application.…”
mentioning
confidence: 99%